A case history of hazardous waste formed in a chemical plant accident - S.Hadzi Jordanov, P.Paunovic, D. Slavkov and A. Dimitrov (Balkan Environmental Association (B.EN.A.), 2002)
Hazardous waste composed of a mixture of chemical products, such as partially burned and/or degraded products – all additives for civil engineering chemistry purposes, and pieces of production hall destroyed in the explosion, different in size and composition, estimated to a total amount of ca. 250 tones was disposed in a nearby mine field for cement industry. Unfortunately, the expectated soon permanent solution failed and, instead of planed 3 to 6 months, it took more than 10 years before further step was realized. During these 10 years a lot of efforts were done aimed to provide a proper solution that will meet the existing legal, environmental, and other regulations. Due to lack of experience, limited finances and other organizational inconcistences, all of the efforts were unsuccessfull. Finally, a solution was found in dislocation of the provisory landfill to an adjacent but already exhausted mine location as the most suitable solution, approved by government authorities as well. For this purpose a three compartment concrete shell (each compartment of ca. 5.5 by 5.5 meters and high 3 meters) was designed, constructed and made watertight. The waste was transferred to the new disposal location, poured out in the shells, compacted and finally covered with an appropriate concrete plate, thus forming a kind of encapsulated sarcophagi. Thorough precaution measures in manipulation were planed and applied in order to prevent any further accident. First of all the existing cell was carefully opened (by drilling a hole) and checked for eventual emission of dangerous (flammable, explosive, poisonous, etc.) gases or vapors. When this possibility was eliminated, the cell was completely opened and samples for physico-chemical testing were picked up. 14 distinguishable samples were taken from the same number of different materials. All samples were tested in the laboratory for leaching in water, change of color, pH and electrical conductivity of the leachate, and organoleptic changes in solid leaching residues. 5 out of these 14 samples were found to give leachate with changes that indicate possible contamination of soil, underground water etc. This finding was a base for the decision that the waste could not be disposed in an open landfill and exposed to interaction with atmospheric precipitations, leading to an eventual environmental threatening. The need for constructing a special disposal cell (as described above) arose from these circumstances, no matter that its price was not at all neglectable. Manipulation with the landfill content, as well its transportation (together with a lot of soil-material) to the new landfill was done carefully and without any spilling. Measures for monitoring any leakage or other possible pollution from the described sarcophagi are planed, no mater that in its content inert soil material or harmless waste are the dominant part. One should be stressed out that this is the very first experience in Macedonia with treatment and legal disposal of hazardous waste.